Ultrasound Targeted Microbubble Destruction Stimulates Cellular Endocytosis in Facilitation of Adeno-Associated Virus Delivery - Jin, Li-Fang (Molecular Diversity Preservation International (MDPI), 2013)
The generally accepted mechanism for ultrasound targeted microbubble destruction (UTMD) to enhance drug and gene delivery is through sonoporation. However, passive uptake of adeno-associated virus (AAV) into cells following sonoporation does not adequately explain observations of enhanced transduction by UTMD. This study investigated alternative mechanisms of UTMD enhancement in AAV delivery. UTMD significantly enhanced transduction efficiency of AAV in a dose-dependent manner. UTMD stimulated a persistent uptake of AAV into the cytoplasm and nucleus. This phenomenon occurred over several hours, suggesting that some viral particles are endocytosed by cells rather than exclusively passing through pores created by sonoporation. Additionally, UTMD enhanced clathrin expression and accumulation at the plasma membrane suggesting greater clathrin-mediated endocytosis following UTMD. Transmission electron microscopy (TEM) revealed that UTMD stimulated formation of clathrin-coated pits (CPs) and uncoated pits (nCPs). Furthermore, inhibition of clathrin-mediated endocytosis partially blocked the enhancement of AAV uptake following UTMD. The results of this study implicate endocytosis as a mechanism that contributes to UTMD-enhanced AAV delivery.